Management and Outcome of Hindfoot Trauma With Concomitant Talar Head Injury. (June 2021) - Engelmann, Esmee Wilhelmina Maria; Wijers, Olivier; Posthuma, Jelle; Schepers, Tim
Background: Talar head fractures account for 2.6% to 10% of all talar fractures and are often associated with concomitant musculoskeletal injuries. The current literature only describes a total of 14 patients with talar head fractures and, with that, guidelines for management are lacking. The aim of the current study was to evaluate the management and long-term outcome of patients who have hindfoot trauma with concomitant talar head fractures. Methods: This study includes a retrospective cohort of patients with talar head fractures. Patient characteristics, trauma mechanism, fracture characteristics, treatment, follow-up, and complications were reported. Functional outcome was assessed using the Foot Function Index (FFI) and the American Orthopaedic Foot & Ankle Society (AOFAS) hindfoot score. Quality of life was measured by the EuroQol-5D (EQ-5D). Twenty-one patients with acute fractures of the talar head were identified. The mean follow-up time was 4.9 years. Results: All patients sustained additional ipsilateral foot and/or ankle injuries. Fifteen patients had operative management of their talar head fracture. There were no postoperative wound infections and no cases of avascular necrosis. All fractures united, and 29% of patients developed posttraumatic osteoarthritis. The overall mean FFI score index was 34.2, and the mean AOFAS score was 70.7. The mean EQ-5D index score was 0.74. Conclusion: Talar head fractures always coincided with other (foot) fractures. Management and long-term functional outcome were affected by the extent of associated injuries. Due to the low incidence and high complexity of talar head fractures, early referral to dedicated foot surgeons and centralization of complex foot surgery is recommended. Level of Evidence: Level IV, retrospective case series.